Fundamental studies of sorghum roughages and grains. A study of the value of pelleting sorghum grain. - Richardson, D.; Smith, E.F.; Koch, B.A.; Cox, R.F.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
Forty Hereford steer calves from the same herd were divided as equally as possible, on the basis of weight and conformation, into four lots of 10 animals each. Two additional steers became available 10 days after the test started and they were added to lot 3. The daily wintering ration consisted of 1 pound soybean oil meal, 5 pounds grain, 2 pounds alfalfa hay, and all the sorghum silage they would clean up. Salt and a mineral mixture of 2 parts steamed bonemeal and 1 part salt were fed free choice. The grain used was as follows: Lot 1, rolled sorghum grain; lot 2, cracked corn; lot 3, finely-ground, pelleted sorghum grain; lot 4, finely-ground sorghum grain. The fattening ration was the same except silage was removed after 32 days. An attempt was made to maintain the same level of grain in all lots.
Keywords: Beef; Pelleting sorghum grain; Roughages